(untitled) (Bangladesh Journal of Zoology, 2019)
The study was conducted to determine growth performances and bioaccumulation of Cr, Cu, Cd, Pb and Ni in fish organs such as intestines, muscle and gills of study species after culturing them for twelve weeks by using different commercial fish feeds. The highest average daily gain (ADG, g/day) and specific growth rate (SGR; %/day) were found in fish fed quality feed and lowest values were found in the fish fed mega feed. Best feed conversion ratio (FCR) value was found in fish fed quality feed among five different feeds. In cultured Koi, the concentration of heavy metals were found higher than initial concentration in fish feeds and collected fingerling samples. Heavy metal levels in cultured fish was Cu > Pb > Cr > Cd > Ni and levels of bioaccumulation in individual organs was intestines > gills > muscle. The concentration of Cu, Pb and Cr exceed the tolerable limit approved by FAO in fishes cultured with the experimental feeds. Considering the present study, Koi cultured with these experimental feeds may not safe for human consumption. Bangladesh J. Zool. 47(1): 77-88, 2019